Double blind, placebo controlled trial of the remission inducing and steroid sparing properties of an ICAM-1 antisense oligodeoxynucleotide, alicaforsen (ISIS 2302), in active steroid dependent Crohn's disease. Issue 1 (1st July 2002) - Yacyshyn, B R; Chey, W Y; Goff, J; Salzberg, B; Baerg, R; Buchman, A L; Tami, J; Yu, R; Gibiansky, E; Shanahan, W R
Abstract : Background and aims: To evaluate the safety and efficacy of the intercellular adhesion molecule 1 (ICAM-1) antisense phosphorothioate oligonucleotide alicaforsen (ISIS 2302) in Crohn's disease. Methods: Active (Crohn's disease activity index (CDAI) 200–350), steroid dependent (prednisone 10–40 mg) Crohn's patients were randomised into three treatment groups: placebo versus ISIS 2302 (2 mg/kg intravenously three times a week) for two or four weeks. Patients were treated in months 1 and 3, with steroid withdrawal attempted by week 10. The primary end point (steroid free remission) was a CDAI <150 off steroids at the end of week 14. Results: A total of 299 patients were enrolled, with a mean baseline CDAI of 276 and steroid dose of 23 mg/day. Rates of steroid free remission were equivalent for the two and four week ISIS 2302 groups (20.2% and 21.2%) and the placebo group (18.8%). At week 14, steroid withdrawal was successful in more ISIS 2302 patients compared with placebo treated patients (78% v 64%; p=0.032). Steroid free remission was highly correlated with exposure (p=0.0064). Other clinical responses were correlated with exposure, with significant results versus placebo being observed in the highest area under the curve subgroup. CDAI scores decreased by 136 (112) at week 14 versus 52 (107) for placebo (p=0.027) and inflammatory bowel disease score questionnaire improved by 43 (31) versus 15 (36) for placebo (p=0.027). Conclusions: Although the primary outcomes failed to demonstrate efficacy, pharmacodynamic modelling suggests that alicaforsen (ISIS 2302) may be an effective therapy for steroid dependent Crohn's disease.